A comparison between adult and paediatric snakebites and their outcomes in North Eastern South Africa. (March 2022) - J, Buitendag; S, Variawa; D, Wood; GV, Oosthuizen
Abstract: Background: Snakebites are common among rural communities. The aim of this study was to ascertain the differences between paediatric and adult snakebite patients regarding severity, management and outcome. Methods: This study included a total of 878 patients admitted to Ngwelezana Hospital, with a snakebite or snakebite-related complication, from September 1, 2008 to December 31, 2014. This included 274 paediatric patients (13 years and younger) and 604 adults. Results: There was a male predominance (56%) in the paediatric group and a female predominance (51%) amongst adults. The duration between the time of the bite and presentation to the hospital was significantly longer in children. The vast majority of children and adults presented with cytotoxic envenomation. Laboratory parameters were worse amongst children in the cytotoxic group. 53 children (19%) and 44 adults (7%) required antivenom administration. Of those who received antivenom, 25% suffered adverse reactions in the paediatric group and 20% in the adult group. 56 Children (20%) underwent one or more procedures on their affected limbs compared to 26 adults (4%). Conclusion: The paediatric population carries a higher risk for serious morbidity and should be treated at a facility with the necessary resources. Children require antivenom more often due to severe envenomation. Delayed presentation carries significant morbidity. Highlights: Snakebites are associated with significant morbidity. Patients should be assessed by experienced providers and monitored continuously. The paediatric population carries a higher risk than adults for serious morbidity. Children require antivenom more often than adults due to severe envenomation. Children are more likely develop antivenom related adverse effects.